ANALYSIS OF CONCRETE COMPRESSIVE STRENGTH AGAINST BAMBOO FIBER WASTE - FARHAN HAWARI; GALI PRIBADI; YONAS PRIMA ARGA RUMBYARSO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
Concrete is a primary construction material consisting of a mixture of cement, water, sand, and aggregate, and often includes additives to improve specific properties such as workability, durability, and setting time (McCormac, 2004). Bamboo fibers, which have a compressive strength of 45.4 MPa (Afdal, 2016) and contain hydroxyapatite (HA), are used as an additive in concrete to improve performance. This study tested the compressive strength of normal concrete and concrete with bamboo fiber variations of 2%, 4%, and 6% at ages of 7, 14, and 28 days, each with two samples per variation (total of 24 test specimens). The test results showed that at 7 days, the 6% variation exhibited the highest compressive strength increase (20.42 MPa) compared to normal concrete (16.37 MPa). However, at 14 and 28 days, only the 6% variation again showed an increase in compressive strength (22.64 MPa), while the 2% and 4% variations tended to decrease compared to normal concrete.